The emotional impact of screening for lung cancer - Bedford, Laura Elizabeth (2017)
Lung cancer is the most commonly diagnosed cancer and the most common cause of cancer related death worldwide. Population-based lung cancer screening programmes have been initiated in the USA and could soon be implemented in other countries. The overarching purpose of this thesis was to explore the emotional impact of lung cancer screening. The research was conducted as part of a clinical trial that was investigating the effectiveness of a blood autoantibody test, EarlyCDT®-Lung, in identifying individuals at the risk of lung cancer.